Penokohan Istri Pandhu Dalam Lakon Kunthi Pilih Sebagai Keteladanan Karakter Wanita Jawa - Dite Hastini; Sarwanto Sarwanto (Widya Wacana: Jurnal Ilmiah, 2022)
This paper describes the results of the intrinsic analysis in the form of the characterization of Dewi Madrim and Dewi Kunthi as the wife of Raden Pandhu Dewanata in the play Kunthi Select the dish of Purbo Asmoro. The characterization of two Pandhu wives can be used as an example of character for the life of Javanese women. This research is a qualitative research using descriptive analysis method by describing the results of the analysis of the intrinsic elements in the Kunthi Select menu of Purbo Asmoro.   Keywords: Characterizations; Exemplary; Javanese woman